SISTEM INFORMASI GEOGRAFIS PERSEBARAN PRODUKSI PADI DI KABUPATEN KEBUMEN TAHUN 2017 DAN 2018 - Bara Setiajati Abdullah (CAPITALIS: JOURNAL OF SOCIAL SCIENCES, 2024)
Kebumen Regency is one of the regencies that has abundant potential food resources. Submission and presentation of information regarding rice production results by BPS Kebumen Regency is still in catalog form and not yet in mapping form. Based on this, it is deemed important to design and build a "Geographic Information System for the Distribution of Rice Production in Kebumen Regency in 2017 and 2018". This research uses web-based information. The result of this research is a geographic information system that is able to provide information in the form of mapping which can help make the process of observing rice production distribution patterns easier and can be used as evaluation material for related parties.